2009
DOI: 10.1111/j.1749-4486.2009.01968.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐cell depletion with rituximab for refractory head and neck Wegener’s granulomatosis: a cohort study

Abstract: Our cohort derived considerable benefit from rituximab permitting a reduction in immunosuppressive exposure and prednisolone dose with few major adverse effects. There was an 80% (4/5) response in patients with retro-orbital granulomas. The effect of rituximab was most noticeable in the first 6 months (88% response).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 25 publications
(31 reference statements)
3
54
0
1
Order By: Relevance
“…In one of the patients, dyspnoea and subglottic stenosis improved significantly after fourth RTX pulse and the disease went into remission, whereas the second patient displayed further disease progression [23]. In some studies, patients with endobronchial and subglottic lesions were not studied in detail [10,22]. We observed no clinical improvement in 3 patients with endobronchial disease nor in two patients with tracheal-subglottic stenosis in response to RTX treatment.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In one of the patients, dyspnoea and subglottic stenosis improved significantly after fourth RTX pulse and the disease went into remission, whereas the second patient displayed further disease progression [23]. In some studies, patients with endobronchial and subglottic lesions were not studied in detail [10,22]. We observed no clinical improvement in 3 patients with endobronchial disease nor in two patients with tracheal-subglottic stenosis in response to RTX treatment.…”
Section: Discussionmentioning
confidence: 58%
“…Of note, ocular biopsy samples from two patients obtained pre-RTX therapy showed the presence of numerous CD20+ cells in the ocular tissue, whereas these cells were undetectable posttreatment [21]. Four of five patients with treatment refractory retro-orbital granuloma responded well to RTX as observed in another retrospective cohort study [22]. However, Aries et al [23] reported in a prospective open-labelled study enlargement of the retro-orbital granulomas in three of five patients, and in other two patients, the granuloma size remained unchanged.…”
Section: Discussionmentioning
confidence: 65%
“…m given every fourth week. Martinez del Pero et al also demonstrated positive response with 1 g dosing in four of five patients with retro-orbital GPA, although two of four responders experienced recurrence after 6 months and required alternative therapy [82]. Similarly, in a recent study evaluating maintenance therapy for systemic GPA, more patients experienced sustained remission with rituximab than azathioprine after induction therapy with corticosteroids and cyclophosphamide [83].…”
Section: Granulomatosis With Polyangitismentioning
confidence: 91%
“…A full clinical response was reported in all cases but 1, who died because of interstitial pneumonia in course ofcyclophosphamide therapy (10). Other cases ofrefractory meningitis -in course of cyclophosphamide therapy -successfully treated with infliximab or rituximab have been reported in recent years (16)(17)(18).…”
Section: Fig 1 Bone Thickening and Hypoattenuation Ofthe Fronto-ethmentioning
confidence: 99%